Postcolonial literatures : Achebe, Ngugi, Desai, Walcott - Parker, Michael; Starkey, Roger (London : Macmillan Press, 1995)
This collection of essays reflects the intensified worldwide debate in literary theories, especially since 1968, and the growth of postcolonial literatures in English. Together they have prompted significant re-readings of cultural histories in Africa, India, and the Caribbean as well as in America and Europe.
Postcolonial Literatures scrutinises the work of four writers, Achebe, Ngugi, Desai and Walcott, and their attempts to find new languages and new narratives to engage with the complex histories of their 'homelands'.
Includes bibliographical references and index.
Keywords: Commonwealth literature (English) -- History and criticism; Decolonization in literature; Nigeria -- In literature; Kenya -- In literature; India -- In literature; West Indies -- In literature